2016
DOI: 10.1021/acs.iecr.6b02080
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Assembled Chitosan-Based Antibacterial Films with Improved Stability under Alkaline Conditions

Abstract: A “post-infiltration and subsequent photo-cross-linking layer-by-layer assembly” strategy was, for the first time, introduced to fabricate carboxylated chitosan (CCS) based antibacterial multilayer films with improved stability under alkaline conditions. Precursory polyelectrolyte multilayers were assembled from CCS and poly­(allylamine hydrochloride) (PAH). 4,4′-Diazostilbene-2,2′-disulfonic acid disodium salt was then infiltrated to cross-link the multilayers under UV irradiation. Analysis by UV–vis spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…As can be seen in Figure 1, there was no light absorbance in the visible range from 400 to 800 nm, indicating that control films and those with EPS were transparent. Additionally, all films absorbed UV light at 200 nm, corresponding to the carbonyl groups in chitosan [28]. Color changes were analyzed by determining L *, a *, and b * parameters, and results are shown in Table 1.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…As can be seen in Figure 1, there was no light absorbance in the visible range from 400 to 800 nm, indicating that control films and those with EPS were transparent. Additionally, all films absorbed UV light at 200 nm, corresponding to the carbonyl groups in chitosan [28]. Color changes were analyzed by determining L *, a *, and b * parameters, and results are shown in Table 1.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Chitosan (Chi) is a β(1→4)-linked copolymer of 2-amino-2-deoxy- d -glucopyranose (GlcN) and 2-acetamido-2-deoxy- d -glucopyranose (GlcNAc) (Figure a) that is mainly produced by carrying out the N-deacetylation of chitin, a polysaccharide abundantly present in the exoskeletons of crustaceans, mollusks, and insects, and also found in the cell walls of some fungi. , Chitosan is nontoxic, biocompatible, and biodegradable and exhibits antitumor, antioxidant, and antimicrobial activities, which make it adequate for several biomedical and biosensing applications. Owing to the presence of the amino groups pertaining to GlcN units, chitosan acquires positive charges in aqueous acid media, displaying the behavior of a cationic polyelectrolyte and enabling its interactions with anionic polymers, such as carboxymethyl cellulose (CMC) (Figure b). Thus, chitosan can be employed to construct layer-by-layer (LbL) assembled polyelectrolyte multilayers, which exhibit promising potential to be used in tissue engineering and as drug delivery systems. As the formation of such structures can be strongly affected by the characteristics of the polymers, the comprehension of the effects of the molecular structures of the constituent polymers on the multilayered architectures produced by LbL self-assembly is fundamental.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, chitosan based sponges have attracted considerable attention in wound dressing applications due to their unique properties and easy preparation. 8 It was reported that chitosan can affect macrophage function which could accelerate wound healing with higher angiogenic capability. 12 It can also stimulate cell proliferation and promote tissue granulation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chitosan is a natural polysaccharide, consisting of randomly distributed N -acetyl- d -glucosamine and β-(1,4)-linked d -glucosamine. , Chitosan is derived from the deacetylation of chitin that can be obtained from the exoskeletons of crustaceans and insects and cell walls of fungi . Chitosan has various biorelated applications because of its excellent unique features, such as large-scale availability, antitumor properties, antibacterial properties, antioxidant properties, various bioactivities, biodegradability, and biocompatibility. Since chitosan has unique chem–physical properties, it can be produced as a drug delivery vehicle, artificial skin, and scaffold in the forms of coatings, beads, sponges, fibers, and membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation